A Dietary Pattern for High Estimated Total Fat Amount Is Associated with Enhanced Allergy Sensitization and Atopic Diseases among Singapore/Malaysia Young Chinese Adults - Lim, Jun Jie; Kavita, Reginald *; Say, Yee How*; Liu, Mei Hui; Chew, Fook Tim (Karger Publishers, 2023)
Introduction: Frequent dietary patterns for fast food diets are suggested to be a risk factor for atopic disease development. Excessive dietary fats in fast foods are postulated to promote low-grade chronic inflammation. However, no studies in Asia have yet to characterize the dietary pattern for high-fat foods with atopic diseases. Thus, this study aims to assess the association between dietary fats with the prevalence of atopic diseases in an allergic cohort.